The Brownings: the reciprocal nature of their genius - Hoffman, Daisy Gladys (My University, 1900)
Introduction: In the protestant cemetery at Florence, Italy, “a place, so beautiful,” says Keats, “that it might make one in love with death to be buried there,” lies the one who the English call “Shakespeare’s Daughter” and Edmund Clarence Stedman names the “Passion Flower of the Century;” there, in the beloved land of her adoption, lies Elizabeth Barrett Browning; and in the beautiful Westminster Cemetery, lies her lovable companion, the one whom we all know as the greatest poet-philosopher, Robert Browning. Early tradition had much to do with the instinctive and complete comprehension of each other’s mental processes; neither had had regular training, but their homes and modes of living were different. Miss Barrett’s father had a wonderful force of character, and of her mother we have no remembrance; while Robert Browning’s father was stern, a lover of good books, and his mother was sweet saint-like, and a lover of Shelly. When Robert Browning was born, on May 7, 1812, in one of the suburbs of London, Miss Barrett had been breathing the pure air of the village Coxhoe Hall for six years. He was sent to school and had every chance to broaden and strengthen himself, but during this period of the poet’s early expansion and recognition, the poetess was becoming more miserable, narrow and externally sad. Her life was melancholy, but possessed within herself the unquestionable and indisputable evidence of unseen things.
Citation: Hoffman, Daisy Gladys. The Brownings: The reciprocal nature of their genius. Senior thesis, Kansas State Agricultural College, 1900.
Morse Department of Special Collections
Keywords: Elizabeth Barrett Browning; Robert Browning; Biography; Theses